An Overview on Indole Aryl Sulfide/Sulfone (IAS) as Anti‐HIV Non‐Nucleoside Reverse Transcriptase Inhibitors (NNRTIs). Issue 4 (19th February 2022) - Sinha, Arun K.; Equbal, Danish; Rastogi, Sumit K.; Kumar, Santosh; Kumar, Ravindra
Abstract: Sulfur‐containing indoles are widely studied against different biological targets. Among several potential drug candidates, seven molecules of this class are in the current market and a few of them are either in pipeline or in different stages of clinical trials. Particularly, arylthioindoles or indolylarylsulfones (IAS) received great attention by medicinal chemists due to their pharmokinetic profiles and wide spectrum of biological activities like antiviral, anticancer, cardiovascular, and antibacterial properties. This review summarizes the developmental process, synthesis and structure activity relationship (SAR) around arylthioindole/indolylaryl sulfone scaffolds for antiviral/anti‐HIV non‐nucleoside reverse transcriptase inhibitor (NNRTIs) activities. It also offers perspective for further development of 3‐indolylarylsulfones as an anti‐viral agent including their potential against novel COVID‐19 infection. Abstract : Indole aryl sulfides/sulfones (IAS) are a significant class of non‐nucleoside reverse transcriptase inhibitors (NNRTIs), which show a wide spectrum of biological relevance specially in antiviral activities. This mini review summerizes the synthesis of Indole aryl sulfides/sulfones with an emphasis on structure activity relationship (SAR) studies to find out the potent anti‐viral candidates. In current scenario, it may help the researcher to develop novel IASs/candidates with potential therapeutic against novel COVID‐19 infection.